2017
DOI: 10.1158/0008-5472.can-16-1546
|View full text |Cite
|
Sign up to set email alerts
|

PAX3-FOXO1A Expression in Rhabdomyosarcoma Is Driven by the Targetable Nuclear Receptor NR4A1

Abstract: Alveolar rhabdomyosarcoma (ARMS) is a devastating pediatric disease driven by expression of the oncogenic fusion gene PAX3-FOXO1A. In this study, we report overexpression of the nuclear receptor NR4A1 is rhabdomyosarcomas which is sufficient to drive high expression of PAX3-FOXO1A there. RNAi-mediated silencing of NR4A1 decreased expression of PAX3-FOXO1A and its downstream effector genes. Similarly, cell treatment with the NR4A1 small molecule antagonists 1,1-bis(3-indolyl)-1-(p-hydroxy or p-carbomethoxypheny… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 48 publications
8
37
0
Order By: Relevance
“…IL-24 also inhibited migration of ARMS cells (Fig. 4F) and these results were similar to those previously observed in ARMS cells transfected siPAX3-FOXO1 (27,32). Supplemental Figure 2 shows by immunostaining of Rh30 cells after transfection with pCMV-6-IL-24 that a large percentage of the cells expressed IL-24.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…IL-24 also inhibited migration of ARMS cells (Fig. 4F) and these results were similar to those previously observed in ARMS cells transfected siPAX3-FOXO1 (27,32). Supplemental Figure 2 shows by immunostaining of Rh30 cells after transfection with pCMV-6-IL-24 that a large percentage of the cells expressed IL-24.…”
Section: Resultssupporting
confidence: 90%
“…Studies in this laboratory have reported that NR4A1 is also overexpressed in RMS tumors compared to normal muscle tissue (27) and NR4A1 regulated many of the same genes/pathways observed in other solid tumors (16,19,20,2732). The NR4A1 ligand 1,1-bis(3-indolyl)-1-(p-hydroxyphenyl)methane (DIM-C-pPhOH) which acts as a receptor antagonist inhibits growth, survival, and migration of RMS cells and also inhibits the NR4A1-regulated PAX3-FOXO1 oncogene and RMS tumor growth in a xenograft mouse model (27,32). The present study was initiated after analysis of RNASeq data showed that knockdown of NR4A1 or PAX3-FOXO1 or treatment with the NR4A1 antagonist DIM-C-pPHOH resulted in a 2- to 27.9-fold induction of the tumor suppressor-like factor interleukin-24 (IL-24).…”
Section: Introductionmentioning
confidence: 90%
“…3C). Previous studies showed that Sp TFs regulate expression of the PAX3-FOXO1 gene in Rh30 cells (13,35). In this study, CF 3 DODA-Me decreased expression of PAX3-FOXO1 in this cell line and this was accompanied by downregulation of PAX3-FOXO1-regulated gene products including NMyc, RASSF4, MyoD1, Gremlin, and DAPK1 ( Fig.…”
Section: Resultssupporting
confidence: 59%
“…Integrin gene promoters are GC-rich, and α6-, α5-, and β4-integrins are regulated by Nur77/Sp1/Sp3/Sp4/p300 complexes ( 51 ). Binding of the Nur77/Sp4 complex to a GC-rich promoter can enhance the transcription of paired box 3 (PAX3)-forkhead box O1 (FOXO1A); furthermore, the expression of Nur77 regulates β1-integrin which, together with PAX3-FOXO1A, contributes to the migration of tumor cells ( 52 ). These effects may be exploited for the development of novel antitumor drugs.…”
Section: Genomic and Non-genomic Functions Of The Orphan Receptor Nurmentioning
confidence: 99%